Pilates exercise and blood test in pregnancy: a systematic review and meta-analysis - Ashifa Quamila; Rezky Amaliah Usman; Desy Annisa Perdana (Physical Therapy Journal of Indonesia, 2024)
Background: While most women perceive pregnancy to be a happy time, there are physiological, anatomical, biochemical, and psychological changes that can occur during this period. Pilates exercise is making strength and endurance for labor and birth. In this sense, this study's purpose was to systematically review the literature on the implication of pilates exercise on blood tests in pregnant women. Methods: Three databases were searched in order to find pertinent publications published up until December 31, 2023. Independently, paired reviewers went through the articles and took data from every study that was included. A meta-analysis was carried out to evaluate how pilates affected the blood test. To investigate heterogeneity, subgroup, and sensitivity analyses were carried out. Results: Ultimately, the meta-analysis containing 32 pregnant women included 4 studies totaling 160 pregnant women. The results of the study demonstrated a significant difference in the levels of total triglycerides (CI95%: -1.627 - -0.104; I2: 16%), total cholesterol (CI95%: -2.210 - 0.027; I2: 17%), and low-density lipoprotein (CI95%: -2.887 - 0.004; I2: 16%) between the pilates exercise group and the control group. The results of the research indicated that the high-density lipoprotein (CI95%: 1.278 - 0.201; I2: 17%) and C-reactive protein (CI95%: -0.556 - 0.579; I2: 18%) levels in the pilates exercise group were considerably lower than those in the control group. Conclusion: We found that pilates exercises are perfect for placenta growth. It can also reduce anxiety and improve physical condition in pregnant women. Therefore, further research and evaluation in clinical trials are needed.